Tinjauan Penggunaan VCCS Terhadap Efisiensi Koordinasi Air Traffic Controller Approach Control Prosedural di Airnav Cabang Bandung - maajid, nuurul; Praptiningsih, Nunuk (Jurnal Bisnis dan Operasi Penerbangan, 2024)
The International Civil Aviation Organization (ICAO) defines coordination in its document Annex 11 - Air Traffic Services as "the process of achieving mutual agreement, through the exchange of information, messages, or other means, between the appropriate ATS units." In the context of air traffic services,coordination involves the exchange of information between different ATS units to ensure safe and efficient flow of air traffic. This includes coordinating the use of airspace, facilitating the transfer of aircraft between different ATS units, and communicating changes in flight plans or weather conditions. Coordination is an essential aspect of air traffic management and helps ensure that all aircraft operating in a specific airspace are safely separated from each other and can follow planned routes without conflict or delay. The voice communication between humans and machines is the idea people have been thinking about a long time. For high level of the voice communication with the control system it is important to ensure good quality of the speech signal processing with additive noise in real environments(Vaňuš, 2011). VCCS in aviation is regulated in the rules established by ICAO in Annex 11, chapter 4. The integrated communication within VCCS includes Very High Frequency transmitters and receivers and telephones. The VCCS at Husein Sastranegara International Airport in Bandung is divided into two interrelated parts: the Remote Control and Monitoring System (RCMS) and the Media Service Center (MSC), with the Voice Control Unit serving as the display. Here are some specifications of the VCCS in Bandung Approach